Acupuncture for polycystic ovary syndrome: An overview of a protocol for systematic reviews and meta analyses. Issue 3 (22nd January 2021) - Liao, Zaibo; Fan, Huaying; Fan, Huayu; Chen, Xiaohua
Abstract: Background: As the results of previous systematic reviews and meta-analyses on acupuncture for polycystic ovary syndrome (PCOS) have provided inconsistent evidence. This overview of systematic reviews (SRs) and meta-analyses will aim to critically appraise the methodology and reporting quality of the relevant SRs and meta-analyses with the aim of identifying whether acupuncture could provide an effective treatment for patients with PCOS or not. Methods: Electronic databases including MEDLINE via Ovid, EMBASE, PubMed, Cochrane library, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journal Database (VIP database), and Wanfang Database will be searched for related SRs and meta-analyses from inceptions to the search date without language restrictions. Two reviewers will independently select SRs and meta-analyses and collect related data, and a third reviewer will be introduced if any disagreement happened during the assessing. The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) and the latest Assessment of Multiple Systematic Reviews 2 (AMSTAR2) checklists will be employed to evaluate the reporting and methodology quality. Results: This overview will be published in a peer-reviewed journal. Conclusion: This overview will identify related SRs and meta-analyses of acupuncture for treating PCOS. Ethics and dissemination: Ethics approval and patient consent are not required as this study is an overview based on published systematic reviews and meta-analyses.